Traffic-Related Air Pollution and "Bikeability" : Quantifying Air Pollution Exposure along Bike Routes in Boston Area - Huang, Hongkun. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Shan Jiang.; Committee: Sumeeta Srinivasan.; Keyword: Urban planning.